Negotiating Space for Living and Tourism in Peneleh Heritage Settlement, Surabaya - Puspitasari, Novi (Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
Heritage tourism has increasingly transformed urban heritage settlements into multifunctional spaces where residential life and tourism activities coexist, creating complex spatial challenges. Despite growing attention to heritage conservation and tourism development, limited research has examined how local communities negotiate shared spaces in living heritage settlements. This study aims to identify the spatial conflicts emerging from the coexistence of residential and tourism functions in Kampung Peneleh, Surabaya, Indonesia, and to formulate strategies for balancing both functions. A qualitative case study approach was employed using field observations and semi-structured interviews with local residents and key stakeholders. The data were analyzed through thematic analysis integrated with spatial interpretation to examine patterns of space use and community perceptions toward heritage tourism activity in their kampong. The findings reveal three major forms of spatial conflict: domesticity versus tourism, mobility versus everyday social activities, and private versus public space. Nevertheless, residents generally perceive heritage tourism positively because of its contribution to local identity and economic opportunities. The study demonstrates that spatial negotiation in heritage settlements is a dynamic socio-spatial adaptation rather than a rigid functional separation. Two complementary strategies are proposed: adaptive small-scale spatial interventions to improve shared spaces and community-based spatial interventions that actively involve residents in planning and governance. This research contributes to the advancement of living heritage and community-based urban design by introducing spatial negotiation as a conceptual framework for balancing heritage tourism and residential functions. Future research should investigate participatory design processes, tourists' spatial behavior, and mechanisms for strengthening community-based local economic development within heritage settlements.